Performance and Microbial Community of Simultaneous Denitrification and Biomineralization in Bioreactors. Issue 3 (5th February 2019) - Su, Junfeng; Bai, Yihan; Huang, Tinglin; Gao, Yichou; Wei, Li; Lu, Jinsuo
Abstract: The effects of combined different strains on a simultaneous denitrification and biomineralization process were examined. The influence of sodium succinate concentration, pH, and hydraulic retention time on nitrate and hardness removal was evaluated in bioreactors. Experimental results indicated that high nitrate and hardness removal efficiencies were obtained under optimum conditions. The community diversity was markedly influenced by the concentration of sodium succinate. The findings proved that Pseudomonas sp. H117 and Pseudomonas sp. H2 played a key role in the process of nitrate and hardness removal. The main component of sedimentation generated from the bioreactor was detected as calcium ion precipitation by scanning electron microscopy and X‐ray diffraction. Abstract : An innovative biotechnological process of simultaneous denitrification and biomineralization in a bioreactor was developed by combining mixed bacteria with ceramsite. The influence of sodium succinate concentration, pH, and hydraulic retention time on nitrate and hardness removal was evaluated. The community diversity was significantly influenced by the concentration of sodium succinate.